(untitled) (Scripta : English Department Journal, 2024)
Teaching and learning vocabulary and pronunciation is challenging for foreign language learning. Currently, the majority of vocabulary and pronunciation teaching in the classroom employs traditional and uninspiring approaches. Conversely, gamification-based technology in the educational environment is believed to facilitate learners’ progress and skills. This study aims to investigate the potential of gamification-based technology media, specifically Duolingo, to enhance prospective English teachers’ English vocabulary and pronunciation skills. This study employed a quantitative approach. The study was conducted at a private university in Jakarta with 72 students as participants. The results of this study indicate that most participants perceive learning a foreign language, particularly vocabulary and pronunciation, through Duolingo as relatively straightforward due to the numerous conversation exercises with diverse vocabulary. Several findings corroborate this regarding Duolingo’s facilities, which include ease of access, variety of topics and information, and a positive effect on learners’ motivation and enthusiasm for learning English. This research implies that Duolingo is an effective tool to support learners in learning foreign languages, especially vocabulary development and English pronunciation, which is easy and enjoyable.